Chloroplast Transformation in Arabidopsis. Issue 4 (27th April 2021) - Ruf, Stephanie; Kroop, Xenia; Bock, Ralph
Abstract: Plastids (chloroplasts) are the defining organelles of plants and eukaryotic algae. In addition to performing photosynthesis, plastids harbor numerous other metabolic pathways and therefore are often referred to as the biosynthetic center of the plant cell. The chloroplasts of seed plants possess dozens of copies of a circular genome of ∼150 kb that contains a conserved set of 120 to 130 genes. The engineering of this genome by genetic transformation is technically challenging and currently only possible in a small number of species. In this article, we describe the methods involved in generating stable chloroplast‐transformed (transplastomic) plants in the model species Arabidopsis ( Arabidopsis thaliana ). The protocols presented here can be applied to (1) target genes in the Arabidopsis chloroplast genome by reverse genetics and (2) express reporter genes or other foreign genes of interest in plastids of Arabidopsis plants. © 2021 The Authors. Basic Protocol 1 : Generation of root‐derived microcallus material for biolistic transformation Basic Protocol 2 : Chloroplast transformation by biolistic bombardment of root‐derived microcalli Basic Protocol 3 : Regeneration of transplastomic lines and seed production